The engineering of actinidin-encoding gene and its expression in Saccharomyces cerevisiae - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Actinidin-encoding gene has been engineered and cloned in an expression-secretion vector designed for yeast Saccharomyces cerevisiae. The engineered actinidin-encoding gene consisted of DNA sequences encoding all N-terminal extension, mature actinidin, and part of C-terminal extension (without amino acids QR-encoding motifs). The variant of actinidin-encoding gene was then expressed in S. cerevisiae and analysed using irrununoblotting technique. Analysis of expression suggested that no product of translation of the gene was detected. It was assumed that the gene may be expressed at transcription and translation level, but the expressed protein may be not be correctly processed and thus has been subjected to proteolytic degradation. Keywords: actinidin âSaccharomyces cerevisiae âprotein secretion